Application of many-body dissipative particle dynamics to determine liquid characteristics. Issue 7 (7th September 2015) - Yamada, Toru; Yuan, Jinliang; Sunden, Bengt Ake
Abstract : Purpose: – The purpose of this paper is to find out the applicability of the many-body dissipative particle dynamics (MDPD) method for various real fluids by specifically focusing on the effects of the MDPD parameters on the MDPD fluid properties. Design/methodology/approach: – In this study, the MDPD method based on van der Waals (vdw) equation of state is employed. The simulations are conducted by using LAMMPS with some modifications of the original package to include the many-body features in the simulation. The simulations are investigated in a three-dimensional Cartesian box solution domain in which MDPD particles are distributed. In order to evaluate the MDPD liquid characteristics for a stationary liquid film, self-diffusivity, viscosity, Schmidt number (Sc) and surface tension, are estimated for different MDPD parameters. The parameters are carefully selected based on previous studies. A set of single-droplet simulations is also performed to analyze the droplet characteristics and its behavior on a solid-wall. Besides, the relationship between the characteristic length in the DPD simulations and scaling parameters for the stationary liquid-film case is discussed by employing the Ohnesorge number. Findings: – The results show that the liquid properties in the MDPD simulations can be widely ranged by varying the MDPD parameters. The values are highly influenced by the many-body feature in the conservative force which is not included in the original DPD method. It is also found that the wetting ability of the MDPD fluid on solid walls can be easily controlled by changing a many-body parameter. The characteristic length between the MDPD reduced unit and real unit is related for the stationary liquid-film case by employing the Ohnesorge number. Originality/value: – The present parametric study shows that the liquid properties in the MDPD method can vary by carefully controlling the MDPD parameters, which demonstrates the high-potential applicability of the method for various real fluids. This will contribute to research areas in multi-phase transport phenomena at nano and sub-micron scales in, for example, fuel cells, batteries and other engineering devices involving porous media.